Effect of a geminate treatment protocol using acupuncture and shockwave therapy to reduce elbow joint pain and improving motor functions among judo players in Diyala clubs - Hani Khalil Ibrahim, (Musamus Journal of Physical Education and Sport (MJPES), 2026)
Objectives. This study aimed to evaluate the effectiveness of a geminate treatment protocol combining acupuncture and ESWT with a structured kinetic rehabilitation program in alleviating elbow joint pain and improving muscle strength and range of motion in judo players.Materials and Methods. A pre- and post-test pilot study was conducted on two experimental groups of 16 participants, divided into two groups of 8, over an eight-week period. Pre- and post-test variables were measured using a VAS for pain, a portable dynamometer for strength, and a gneumeter for range of motion. T test was used for related and independent samples, and effect sizes (Cohen's d) and variance ratios (η²) were calculated, with a significance level α = 0.05.Results. The group that received the geminate protocol showed statistically and practically significant improvement, with mean pain decreasing from 6.31 ± 0.74 to 2.10 ± 0.62 (t = 9.04, p < .001, d = 2.10), and strength increasing from 27.3 ± 2.48 to 32.1 ± 2.15 (t = 6.42, p < .001, d = 1.70). Range of motion increased from 104.6 ± 3.85 to 118.2 ± 3.10 (t = 7.15, p < 0.001, d = 1.85).The second group (prickling + motor program) also recorded significant improvements, but with smaller effect sizes: pain 6.28 → 3.40 (t = 5.82, p = .001, d = 1.35).In post-test comparison, the geminate protocol demonstrated superiority across all variables: pain difference (t = −4.12, p = 0.001, d = 1.45, η² = 0.46), strength (t = 2.50, p = 0.022, d = 0.90, η² = 0.28), and range of motion (t = 5.56, p < 0.001, d = 1.95, η² = 0.61).Conclusion. The study concludes that integrating ESWT and acupuncture with a rehabilitation program provides a comprehensive therapeutic effect that exceeds the effectiveness of acupuncture and exercise alone, achieving significant pain relief and strong functional improvements in strength and flexibility. The study recommends adopting this geminate protocol in sports rehabilitation programs, training staff in its application, and conducting research with larger sample sizes and longer follow-up periods to confirm the sustainability of benefits.